Development of a Model of Porcine Epidemic Diarrhea in Microminipigs. Issue 5 (September 2019) - Kawaguchi, Hiroaki; Horie, Masayuki; Onoue, Koki; Noguchi, Michiko; Akioka, Kohei; Masatani, Tatsunori; Miura, Naoki; Ozawa, Makoto; Tanimoto, Akihide
Porcine epidemic diarrhea virus (PEDV) induces an often fatal gastrointestinal disease in piglets. In this study, we performed a PEDV infection experiment with the Microminipig, the smallest of experimental minipigs, as a novel small animal model. We orally inoculated a neonatal Microminipig with an intestinal homogenate of a PEDV-infected pig and housed it in a small cage originally designed for rats in an animal biosafety level 2 facility. The infected Microminipig showed the typical signs of porcine epidemic diarrhea (PED), such as watery diarrhea, loss of appetite and weight loss. We also recognized a high amount of excreted PEDV in its rectal swabs and villus atrophy of the small intestine. These results suggest that the Microminipig is a good small animal model for PED, which may contribute to a better understanding of the pathogenesis of PEDV.